Analisis Usaha Ternak Sapi Perah Di Kecamatan SeloKabupaten Boyolali - Puspitasari, Ayu; , Dra. Hj. Umrotun, M.Si; , Drs. H. Yuli Priyana M.Si (2016)
Research analysis of dairy cattle business in district Selo aims to 1) knowing how the characteristics of dairy farmers in the village of Lencoh and the village of Samiran. 2) analyze the difference of physical and non-physical factors in the village of Lencoh and the village of Samiran towards milk production. 3) know the donations income from dairy cattle results against the total income of the family. This study used a survey method, for determining the method of purposive sampling area using this selected based on certain considerations, whereas in sampling the study using the method of random proportional sampling as much as 50% in the village and the village of Lencoh and Samiran who become the respondents as much as 39 breeders. For the analysis of the data using Analysis tables that include cross-tabulations and frequencies are tabulated. Tabulate the frequency analysis aimed to know the characteristics and variable, whereas the cross tabulations analysis aims to find out whether or not there is a relationship between variables and variable influence affected. The data collected in this research is the primary data and secondary data. From these data then known characteristics in region research varied where breeders from breeders more aged among productive, for education in the area of research at most graduates completed elementary, for research in matapencahrian in addition to being a breeder as well as farmers and ranchers for the number of members of the family consisting of 3-5. The motivation of doing business farms in the area of penelian is to increase revenue. Physical factors that become an obstacle is the difficulty of water and non-physical barriers are the existence of price differences between pengepul and KUPT Sido forward. The presence of the addition income from dairy cattle business.